Defining the Perception of Professional Integration: The Case of Workers Aged 45 and Over Experiencing Professional Instability - Fournier, Geneviève; Gauthier, Christine; Zimmermann, Hélène (Canadian Journal of Counselling and Psychotherapy, 2011)
This article deals with the perception of professional integration among workers aged 45 years and over experiencing professional instability. Based on qualitative interviews with 78 Francophone workers in Quebec in non-standard employment for at least three years, the analysis enabled us to develop a pluridimensional definition of the perception of professional integration and to identify four distinct levels. These levels reflect the complexity of the situations experienced by these workers and the diverse meanings persistent non-standard employment had for them at this stage of their life. Finally, some suggestions for counselling intervention are briefly discussed.